Contemporary Reflections on Abuse of Authority in the Coastal Wall Project within the Framework of Sharia Economic Law - lombo, Juliandre Lombo; Rungarun Boonsayan (Islamic Research Publiser, 2025)
This study aims to analyse the case of abuse of authority in the coastal wall construction project in Tangerang, Banten, from the perspective of Sharia Economic Law. The case drew attention due to maladministration, document forgery, and the illegal issuance of land ownership and building use rights certificates, resulting in the loss of fishermen's access to their traditional fishing grounds and causing economic losses of up to IDR 24 billion. This study addresses two main questions: (1) What forms of authority abuse occurred in the project? Moreover, (2) How do the principles of Sharia Economic Law, such as trust (amanah), justice ('adil), and public benefit (maslahah), assess such actions? The research employs a qualitative approach, utilising a normative-juridical method and a comparative sharia perspective, which involves content analysis of legal documents, investigative reports from state institutions, and literature in fiqh muamalah. The findings show that the abuse of authority not only violates Indonesian positive law but also contradicts key principles of Sharia Economic Law. The absence of the sharia-based tenets in public governance contributes to social inequality, loss of public trust, and ethical decay in resource management. The study concludes that integrating the national legal system with the values of Sharia Economic Law is essential to prevent power abuse and enhance the accountability of public officials.This research presents an alternative framework based on maqāṣid al-sharī‘ah for the ethical evaluation of public policies, serving as an early reference for applying Sharia Economic Law in cases of authority abuse in infrastructure development.